Distribuição da classe Thaliacea (Tunicata) em frente a costa do estado do Rio de Janeiro - Bonecker, Sérgio Luiz Costa (1983)
Plankton was sampled at 63 station's during “Operação Rio de Janeiro I” in horizontal, vertical and oblique plankton hauls. The class Thaliacea was studied through the ohservation of 17.928 organims divided in 6 species: Salpa fusiformis, Thalia democratica, T. cicar, Doliolum nationalis Doliolum gegenbauri and Pyrosoma atlanticum. Various fases of life cycle of these species were observed and for the first time in brazilian coast water a young colonie of Pyrosoma atlanticum was appointed. The Thalia democratica and Thalia cicar separation was discussed. The resultd obtained through the horizontal distribution of the "Standing-stock" (org/100m3) of Thaliacea were compared wiht plankton biovolume and correlated with temperature and salinity data.